Analisis Sistem Pengendalian Internal dalam Optimalisasi Sistem Pembelian pada PT. Mulia Safety Service Surabaya - Mersiana Varia Juita (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2021)
This study aims to describe the application of the purchasing accounting system in the company and evaluate the internal control system in the company's purchasing accounting system. This research utilizes qualitative methods. The scope of research conducted in this study is an evaluation of internal control in the purchasing system at PT. Mulia Safety Service, which is located at Jl. Eastern Silver No. 232, Surabaya. Total respondents were determined using the snowball sampling technique—respondents who were selected to be key informants from the information manager of PT. Mulia Safety Service, then continued to other respondents based on recommendations from key respondents with assumptions related to the research conducted. Meanwhile, data analysis was carried out by collecting data, reducing data, presenting data, and analyzing data. The results showed that the internal control system for the purchasing accounting system at PT. Mulia Safety Service Surabaya is still not comprehensive. This is due to the dual function of the purchasing department (purchase function and receiving function) and the lack of document distribution (goods receipt form), which should also be accepted by the accounting department. Therefore, some improvements are needed. First, by creating a separate receiving section as a reception function or by giving this authority to the inventory section, and secondly, the receiving function also creates documents (goods receipt forms) so that not only the purchasing and inventory departments receive them but also the accounting department. This improvement is expected to optimize the purchasing accounting system at PT. Mulia Safety Service Surabaya.